Transformation of Public Services Through Electronic-Based Government System in Malang City - Bayu Karunia Putra; Charis Bagus Dhanuarta (Peneliti.net, 2021)
The electronic-based government system is a transformation in the process of providing public services, both internally and externally through technical operations of information and communication technology to improve the quality of public services. It has also been explained, in Presidential Regulation no. 95 of 2018 concerning the Electronic-Based Government System which regulates the National SPBE Master Plan and the integration of electronic services. Thus, public services that have been able to be carried out through a direct interaction process, then with the presence of increasingly sophisticated information and communication technology can provide convenience in providing services through digital devices. The purpose of this study was to determine how effective and efficient the implementation of the model related to